CGIAR’s submission of its views on the tenth technical expert dialogue and the second meeting under the ad hoc work programme on the new collective quantified goal on climate finance - Chilambe, Pedro; Kinyua, Ivy; Ouedraogo, Issa; Colombo, Chiara; Bowa, Emma; Mukherji, Aditi (2024)
CGIAR welcomes the outcomes from COP28 regarding Decision 8/CMA.5 on the New Collective Quantified Goal on Climate Finance and extends its support to the facilitation of science- based evidence to support the definition of the goal, including the structure, time frame, scope, and sources of funding in respect to food, land, and water.